Screening for coeliac disease in children and adults living in a slum of Dhaka, Bangladesh. Issue 1 (20th April 2019) - Gazi, Md. Amran; Das, Subhasish; Mahfuz, Mustafa; Hasan, Md. Mehedi; Hossain, Md. Shabab; Fahim, Shah Mohammad; Alam, Md. Ashraful; Noor, Zannatun; Gilchrist, Carol A; Petri, William A; Rahman, M Masudur; Mazumder, Ramendra Nath; et al.
Abstract : Background and objective: Serological screening with a confirmation through biopsy has improved the understanding of coeliac disease (CD) epidemiology worldwide. Prevalence of CD in Bangladesh is not yet explored and therefore, we aimed to assess the seroprevalence of CD in slum-dwelling malnourished children and adults in Dhaka. Methods: Serum samples were collected from three different cohorts: stunted (length-for-age Z-scores (LAZ) <−2) and at risk of stunting children (LAZ <−1 to −2) and malnourished adults (body mass index <18.5 kg/m 2 ). Samples from all the participants were assessed for anti-tissue transglutaminase antibody (tTG-IgA) and total serum IgA by ELISA. Positive tTG-IgA and randomly selected low IgA values were reconfirmed using anti-tTG-IgG and gliadin IgG ELISA. CD was diagnosed when second screening tests were found positive and the participants were further investigated by small bowel biopsy. Results: A total of 818 participants (240 stunted, 272 at risk of stunting children and 306 malnourished adults) were enrolled in the study. Overall, anti-tTG-IgA was positive in 5/818 (0.6%; 95% CI 0.25% to 1.46%). Of the five positive cases, anti-tTG-IgG and gliadin IgG were found positive in only one participant. Duodenal biopsy of positive participant revealed characteristic lesions of CD. Randomly selected low IgA values were found negative in tTG-IgG and gliadin IgG for all the participants. No participant was found total IgA deficient. Conclusion: The incidence of coeliac autoimmunity is low in malnourished slum dwellers regardless of age in Bangladesh. It is important to investigate the nationwide prevalence to reveal the definite picture.